Leading article: (Trans)disciplinary research (re)considered - Le Grange, L. (South African Journal of Higher Education, 2017)
In this article I review the emergence of transdisciplinary research and in particular the integrative approach to this category of research. I examine the potential of the integrative approach to achieve cognitive justice – whether it decentres Western science and gives equitable treatment to other ways of knowing such as indigenous knowledge. I aver that transformations that have occurred within discourses on transdisciplinary research have not changed the Western cultural archive itself and that Western science continues to dominate other ways of knowing in the integrative approach in transdisciplinary research. I draw on insights from Deleuze and Guattari to open up ways of reimagining transdisciplinary research as a decolonising process.